GENERAL CHARACTERISTICS OF LEVELS AND TYPES OF INTERCULTURAL COMMUNICATION - Marjona Mukhammadjonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The general characteristic of all levels and types of intercultural communication is discussed in the article about the cultural differences of its participants.